Electronic Module Development Based on Local Wisdom Using Canva Application in History Subject in Class XI IPS 1 SMA Negeri 1 Banawa - Nur Afni Setia Putri; Hasan; Misnah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The problem in study This is : (1) How connection module electronic based on wisdom local to application canva on eyes lesson history (2) How development eye lesson history (3) How results development module electronic based on wisdom local use application canva on eyes lesson history . Research objectives This is : (1) To describe connection module electronic based on wisdom local to application canva on eyes lesson history (2) Describe development eye lesson history (3) Analyze results development module electronic based on wisdom local use application canva on eyes lesson history . Type of research using Research and Development (R&D) with the ADDIE development model ( Analysis, Design, Development, Implementation, and Evaluation ). Research This conducted at SMA Negeri 1 Banawa. Subject in study This is a module development electronic based on wisdom local use application canva to participant educate class XI IPS 1, totaling 33 participants students who are in One class . The data collection technique used in this study was carried out using an expert questionnaire sheet consisting of material experts, media experts , and a questionnaire sheet of student responses to the developed learning media. The results of the study show eligibility module electronic based on wisdom local use application canva assessed by one media expert and expert material . Based on evaluation obtained results from expert material by 87% and is included in the very decent category whereas from media experts by 76% and including category worthy . As for the response participant educate in groups small reach score percentage 94.25 % are included in the very interested category , while in the interested group big or field reach score percentage 93.75 % are included in the very interested category . In general overall module electronic can used for the learning process .